2006
DOI: 10.1063/1.2158502
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent band gap of colloidal quantum dots

Abstract: The size-dependent band gap of semiconductor quantum dots is a well-known and widely studied quantum confinement effect. In order to understand the size-dependent band gap, different theoretical approaches have been adopted, including the effective-mass approximation with infinite or finite confinement potentials, the tight-binding method, the linear combination of atomic orbitals method, and the empirical pseudopotential method. In the present work we calculate the size-dependent band gap of colloidal quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
211
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(239 citation statements)
references
References 22 publications
15
211
0
4
Order By: Relevance
“…The most important characteristic of these nanostructures is very high surface to volume ratio. As a result, surface effects which are negligible in the bulk material, can lead to a significant changes in the mechanical [1,2], thermal [3,4], electronic [5][6][7] and structural [8][9][10][11][12] properties of the nanostructures which are very different from their bulk counterparts. The properties of the nanoparticles can be tuned by functionalizing the nanoparticle by other organic/inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The most important characteristic of these nanostructures is very high surface to volume ratio. As a result, surface effects which are negligible in the bulk material, can lead to a significant changes in the mechanical [1,2], thermal [3,4], electronic [5][6][7] and structural [8][9][10][11][12] properties of the nanostructures which are very different from their bulk counterparts. The properties of the nanoparticles can be tuned by functionalizing the nanoparticle by other organic/inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…This potential cascade design induces an additional built-in electric field and serves as a driving force, which improves the minority carrier transport in device demonstrations. Longer wavelength photons were absorbed closer to the junction, which increased the FF of a graded solar cell [39]. A subsequent study demonstrated efficient exciton transfer mechanisms in EDT-and 1,3-BDT-treated funnels, resulting in enhanced carrier transport and photocurrent [226].…”
Section: Quantum Funnelsmentioning
confidence: 95%
“…Though the true costs of scaling up CQD solar cell manufacturing to the gigawatt power scale are unknown, they are expected to be similar to those for organic photovoltaics [36] because of the similarities in materials, synthesis, and growth processes involved in the two technologies. Second, the steady rise in device efficiencies may indicate that CQD films combine the benefits of bulk semiconductors with those of solution-processed molecular materials [37][38][39]. Third, CQDs possess unique optical and electrical properties that could potentially be harnessed in strategies for overcoming the single junction ShockleyQueisser efficiency limit [40].…”
Section: Introductionmentioning
confidence: 99%
“…This band gap depends on the size of the nanocrystals. 21 Hence, we want to find the energy levels by solving the Schrodinger's equation for the electron-hole system in the semiconductor. For this calculation, the terms that should be considered in the Hamiltonian of the systems are (i) kinetic energy of the electron and holes, (ii) the confinement potential and (iii) the Coulombic interaction between electron and hole.…”
Section: Confinement Of Charge Carriers In Nanocrystalsmentioning
confidence: 99%